Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1710-1492-9-16
|View full text |Cite
|
Sign up to set email alerts
|

A four-way, double-blind, randomized, placebo controlled study to determine the efficacy and speed of azelastine nasal spray, versus loratadine, and cetirizine in adult subjects with allergen-induced seasonal allergic rhinitis

Abstract: BackgroundAzelastine has been shown to be effective against seasonal allergic rhinitis (SAR). The Environmental Exposure Unit (EEU) is a validated model of experimental SAR. The objective of this double-blind, four-way crossover study was to evaluate the onset of action of azelastine nasal spray, versus the oral antihistamines loratadine 10 mg and cetirizine 10 mg in the relief of the symptoms of SAR.Methods70 participants, aged 18-65, were randomized to receive azelastine nasal spray, cetirizine, loratadine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…The EEU has proven effective in multiple studies evaluating various aspects of seasonal allergic rhinitis and its treatments [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Previous studies conducted in the EEU using ragweed pollen have shown 3500 grains/m 3 ± 500 to be an optimal concentration to produce symptoms similar to those experienced in the outdoor environment.…”
Section: Introductionmentioning
confidence: 99%
“…The EEU has proven effective in multiple studies evaluating various aspects of seasonal allergic rhinitis and its treatments [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Previous studies conducted in the EEU using ragweed pollen have shown 3500 grains/m 3 ± 500 to be an optimal concentration to produce symptoms similar to those experienced in the outdoor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the EEU was used to examine azelastine nasal spray vs. orally administered cetirizine, loratadine, or placebo [57]. Azelastine nasal spray significantly reduced nasal symptoms, compared with placebo, and exhibited a faster onset of action compared to oral treatments [57].…”
Section: Intranasal Antihistamine And/or Steroid Formulationsmentioning
confidence: 99%
“…The patient or family was asked to score between 0 and 3 for each of four main symptoms of AR (nasal obstruction, sneezing, discharge, pruritus) (Table 1). Thus, TSS scores ranged between 0 and 12 (14).…”
Section: Methodsmentioning
confidence: 99%